[quotation] On planners - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1999)
On planners: 'If these people plan above our heads, without consulting us, how can we develop? We will follow their plans because they are experts , they are the authority, but the plan can only fail if they don t consult us' a group of...